Diversity and Complexity of Religion and Spirituality in Iran: Relationships With Self-Compassion and Self-Forgiveness. Issue 4 (2nd October 2017) - Ghorbani, Nima; Watson, P. J.; Kashanaki, Hamed; Chen, Zhuo Job
ABSTRACT: This study examined religious-spiritual types in Iran by comparing seminary and university students on self-compassion, self-forgiveness, and other measures of religious and psychological functioning. Islamic seminarians ( N = 198) more frequently self-identified as both religious and spiritual or as religious only. University students ( N = 302) more commonly described themselves as spiritual only or as neither spiritual nor religious. The both religious and spiritual type was highest in religious commitment, self-compassion, and psychological adjustment, with the neither religious nor spiritual type tending to score lowest. The religious-only type displayed the lowest self-forgiveness. Seminarians were also lower in self-forgiveness, but otherwise higher than university students in their mental health. In correlations, self-compassion was compatible, but self-forgiveness was incompatible with Muslim commitments. Muslim spirituality moderated Muslim attitude relationships. These data documented the diversity and complexity of religion, spirituality, and perspectives on the self in Iranian Muslims.